The effects of leadership competencies and quality of work on the perceived readiness for organizational change among nurse managers. Issue 4 (2nd October 2017) - Al-Hussami, Mahmoud; Hamad, Sawsan; Darawad, Muhammad; Maharmeh, Mahmoud
Abstract : Purpose: This paper aims to set a leadership guidance program that can promote nurses' knowledge of leadership and, at the same time, to enhance their leadership competencies and quality of work to promote their readiness for change in healthcare organizations. Design/methodology/approach: A pre-experimental, one-group pretest-posttest design was utilized. Out of 90 invited to participate in this study, 61 nurses were accepted to participate. Findings: The statistical analyses suggested several significant differences between pre- and in-service nurse managers about leadership competencies, quality of work and readiness for change. Yet, findings from the background characteristics were not found to be significant and had no effects on the perceived readiness for change. Research limitations/implications: The present study highlights the importance of leadership competencies and quality of work that healthcare policymakers identify for the success of organizational change efforts. Practical implications: Healthcare policymakers, including directors of nursing, should focus on applications that increase leadership competencies and overall satisfaction of the nurse managers to support the changes in hospitals and supporting learning organization. Hence, they should establish policies that decrease the possible negative impact of planned change efforts. Originality/value: Competent nurse managers enhance their readiness for change, which in turn helps nurses in constructive change processes. A leadership guidance program should be set for nurse managers. This study has important implications for hospital administrators and directors of nursing.